Review on Phytochemical and Pharmacological Aspects of Cichorium intybus Linn. - Gupta, S.K.; Ansari, S.H. (Asian Journal of Chemistry, 2016)
Cichorium intybus Linn. (Compositae) is an important medicinal plant which finds use in Ayurveda and Unani systems of medicine, especially in inflammations. It is useful in thirst, headache, ophthalmia, throat inflammation, enlargement of the spleen, fever, vomiting and diarrhea, etc. An attempt has been made to review the phytochemical and pharmacological work done on Cichorium intybus Linn.